The Role of Industry Sensitivity in Moderating The Effect of Environmental, Social, and Governance (ESG) on Financial Distress - Luthfi, Ahmad; Atmini, Sari (E-Jurnal Akuntansi, 2025)
This study aims to analyze and obtain empirical evidence on the effect of Environmental, Social, and Governance (ESG) on financial distress, and the role of industry sensitivity in strengthening the effect of ESG on financial distress. The research sample selected through purposive sampling consist of 108 Morningstar Sustainalytics rated companies listed on the Indonesia Stock Exchange in 2024. The results of the data analysis utilizing Moderated Regression Analysis (MRA) exhibit that ESG has a significant negative effect on financial distress, suggesting that the higher the ESG performance, the lower the risk of financial distress. However, contrary to the proposed hypothesis, industry sensitivity significantly weakens the negative effect of ESG on financial distress. Keywords: ESG; Financial Distress; Industry Sensitivity; Z-Score; ESG Rating.